IMPLEMENTATION OF MENTAL TRAINING TO ENHANCE ACHIEVEMENT MOTIVATION IN AMPUTEE FOOTBALL ATHLETES - Kurnia Darisman, Eka; Hanafi , Moh.; Hananto Puriana, Ramadhany; Margisal Utomo, Gatot; Fefrian Rosmi , Yandika; Rahman Sanjaya , Yoga; Candrika , Agatha; Erlangga, Wahyu (Journal of Social Comunity Services, 2025)
Objective: The objective of this study is to analyze the role of mental training in enhancing the psychological readiness of amputee football players to optimize their performance under competitive pressure. Method: The study focuses on three primary techniques of mental training: concentration, relaxation, and mental imagery. These techniques are systematically applied to address psychological challenges faced by amputee football players during competitions, enabling them to manage stress and maintain focus effectively. Results: Findings indicate that structured mental training significantly enhances athletes' ability to handle competitive stress, improving their psychological preparedness. This improvement positively influences their overall performance, complementing their physical, technical, and tactical skills. Novelty: This study highlights the unique psychological challenges faced by amputee football players and emphasizes the necessity of tailored mental training programs. It offers a specialized approach to support athletes with special needs, integrating mental preparation as a core element of their training regimen.